Adaptación de la Universidad Técnica de Babahoyo a la educación online post covid19 - Ramos Morocho, Raúl Armando (2020)
This article analyzes the adaptation that was carried out within the Technical University of Babahoyo to coexist with the effects of the pandemic in relation to face-to-face academic activities. Virtual learning environments constitute an academic tool that perfects the learning process, being a fundamental didactic resource in the daily curricular activities of teachers in these difficult moments. In order to demonstrate the results, a field study was carried out with a sample of 211 teachers, including tenured and contracted from the total population, which is 463 from the UTB. The implementation of technological strategies that make it possible to cope with academic activities is analyzed and a growth in the use of the MOODLE platform is noted, which went from 30% of use by teachers to 100%. But, without a doubt, within the use of virtual learning environments there are benefits such as: better interaction with the student, greater flow of information, improved collaborative learning and, above all, flexibility in time and its coverage. Finally, the conclusions of the present investigation are exposed to promote new questions susceptible to future investigations.